2012
DOI: 10.1111/jonm.12015
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to burnout among Chinese female hospital nurses: cross-sectional survey in Liaoning Province of China

Abstract: Occupational stress was identified as the most robust predictor of burnout among Chinese female hospital nurses. Reducing burnout among nurses working in China may require health education, health promotion and occupational training programmes aimed at improving work situations and reducing occupational stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
46
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 25 publications
10
46
4
Order By: Relevance
“…, Wu et al . ). Higher levels of education, knowledge and qualifications might increase burnout among social workers due to them feeling overqualified and thus becoming bored and frustrated (Wu et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Wu et al . ). Higher levels of education, knowledge and qualifications might increase burnout among social workers due to them feeling overqualified and thus becoming bored and frustrated (Wu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Burnout occurs when stress is not mediated or cannot be reduced, 33 and job stress can increase the chance of burnout. 34 Therefore, job effort and reward were the most important of the three burnout symptoms in this study. Future organizational coping strategies should focus on decreasing work load, providing stress management training, and developing rewards to decrease the E/R ratio in order to reduce the risk of burnout among COs. Interestingly, overcommitment had a positive effect on PE.…”
Section: Discussionmentioning
confidence: 98%
“…PE measures one's perception of competency and success at work. 34 It is a separate and distinct outcome variable related to burnout symptoms among COs. Moreover, it was found that the sense of PE among COs is more closely tied to concrete, quantitative goals than that of other human service occupations whose tasks are less structured.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations